2009
DOI: 10.1253/circj.cj-08-0851
|View full text |Cite
|
Sign up to set email alerts
|

Re-Restenosis and Target Lesion Revascularization After Treatment of Sirolimus-Eluting Stent Restenosis Retrospective Analysis From 4 Japanese Hospitals

Abstract: Circ J 2009; 73: 867 -871 ecently randomized trials have demonstrated that drug-eluting stents (DES) substantially reduce in-stent restenosis and the need for repeat revascularization compared to bare metal stents. 1,2 However, in-stent restenosis remains an important clinical problem especially in highly complex lesions. 3 There is limited information about the optimal management of DES restenosis. This study evaluated the incidences of angiographic re-restenosis and re-target lesion revascularization (TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…The TLR rate at 1 year after sirolimus-eluting stent was only 1.4% in the recent ZEST trial (Park SJ et al, presentation at the late breaking clinical trial session of the American College of Cardiology 58th Annual Scientific Session and i2 Summit), and incidence of definite/probable ST was only 0.91% at 2 years in the j-Cypher registry. 15, 16 Regardless of the cause of variance between the current and previous studies, our registry demonstrates favorable long-term clinical outcomes following DES implantation for the treatment of coronary bifurcation lesions in a real-world practice.…”
Section: Drug-eluting Stents For Bifurcationmentioning
confidence: 67%
“…The TLR rate at 1 year after sirolimus-eluting stent was only 1.4% in the recent ZEST trial (Park SJ et al, presentation at the late breaking clinical trial session of the American College of Cardiology 58th Annual Scientific Session and i2 Summit), and incidence of definite/probable ST was only 0.91% at 2 years in the j-Cypher registry. 15, 16 Regardless of the cause of variance between the current and previous studies, our registry demonstrates favorable long-term clinical outcomes following DES implantation for the treatment of coronary bifurcation lesions in a real-world practice.…”
Section: Drug-eluting Stents For Bifurcationmentioning
confidence: 67%
“…Focal restenosis was associated with lower incidence of target lesion failure compared with nonfocal restenosis in the case of treatment with bare-metal stent 13 and SES. 8,9 Previous reports demonstrated that focal restenosis remained the most common pattern (71.3% to 79.0%) with SES in real-world clinical practice. 14,15 Although we could not fully address the pattern of restenosis in the current analysis, it is possible that the prevalence of nonfocal restenosis might increase with increasing complexity of the original target lesions.…”
Section: Discussionmentioning
confidence: 96%
“…For focal restenotic lesions, the incidence of TLR after drug-eluting stent implantation and BA treatment was 8.6% and 11.4%, respectively, whereas for nonfocal restenotic lesions, incidence was 22.6% and 24%, respectively. Kitahara et al 9 reported that in 101 patients with 102 lesions undergoing TLR for SES-associated restenosis, recurrent TLR tended to be lower with SES implantation than with treatment with BA, both in the focal type (12.5% versus 35.5%) and in the nonfocal type (35.3% versus 50.0%), respectively, during the mean follow-up of 13.0Ϯ8.9 months. Angiographic analysis in the present study demonstrated consistent reduction in the rate of recurrent TLR by use of repeated SES implantation in both the focal-type and the nonfocal type SES-associated restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown similar benefits between repeat DES stenting and conventional balloon angioplasty, whereas others have shown clear benefit for repeat DES stenting. [2][3][4] Percutaneous coronary balloon angioplasty has been largely superseded by repeat DES stenting or the 'sandwich stenting' technique, which is steadily gaining prominence. 5) We report a case of recalcitrant target lesion ISR which was successfully treated with drug-eluting balloon deployment.…”
mentioning
confidence: 99%